Unnatural definitions for natural experiments: a call for clarity when estimating causal effects of interventions - Sam Harper; Jay Kaufman; Arijit Nandi (Journal of Epidemiology and Community Health, 2026)
The term 'natural experiment’ has a murky conceptual history in public health, with definitions ranging from naturally occurring states to unspecified approximations of randomised trials. Craig and colleagues recently defined natural experiments as events creating exposed and unexposed groups outside researcher control, but this is largely indistinguishable from any observational study. One could define natural experiments as cases of randomised treatment assignment by a third party but expanding beyond this creates complications. We argue that grouping study designs with labels like 'natural experiments’ or 'quasi-experiments’ provides potentially misleading guidance for causal inference given the difficulty of justifying the core assumption of ‘as-if randomisation’ across diverse designs. Rather than relying on vague labels, researchers should explicitly state their design and defend the credibility of assumptions needed for causal inference. Expansive definitions of ‘natural experiments’ can potentially bias evidence synthesis by obscuring the rigorous justifications needed for causal inference, ultimately creating more confusion than clarity.